2016
DOI: 10.1039/c6ra20250k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dye-sensitized solar cells based on CNT-derived TiO2 nanotubes and Nb-doped TiO2 nanoparticles

Abstract: We report the use of Nb-doped TiO2 photoelectrodes incorporating CNT-derived TiO2 nanotubes as a facile strategy to enhance the efficiency of DSSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For instance, one-dimensional (1D) TiO 2 including TiO 2 -tubes, TiO 2 -rods, TiO 2 -bers, TiO 2 -belts, and TiO 2 -wires recently have attracted wide interest for photoelectrical applications because of their large surface area for light-absorption, as well as an axial transport of photo-generated carriers with fast transport property. [13][14][15][16][17][18] In addition, forming a Schottky or p-n junctions to realize band structure engineering is another effective approach, which aims to widen the visible light-absorption and hinder from the recombination of electrons and holes to improve the photon-to-energy conversion efficiency. [19][20][21] For example, coupling 1D TiO 2 with narrow bandgap zerodimensional (0D) quantum dots could enhance the photoconductivity by photogating effect.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one-dimensional (1D) TiO 2 including TiO 2 -tubes, TiO 2 -rods, TiO 2 -bers, TiO 2 -belts, and TiO 2 -wires recently have attracted wide interest for photoelectrical applications because of their large surface area for light-absorption, as well as an axial transport of photo-generated carriers with fast transport property. [13][14][15][16][17][18] In addition, forming a Schottky or p-n junctions to realize band structure engineering is another effective approach, which aims to widen the visible light-absorption and hinder from the recombination of electrons and holes to improve the photon-to-energy conversion efficiency. [19][20][21] For example, coupling 1D TiO 2 with narrow bandgap zerodimensional (0D) quantum dots could enhance the photoconductivity by photogating effect.…”
Section: Introductionmentioning
confidence: 99%
“…Among n-type-doped TiO 2 systems, Nb-doped TiO 2 photoanodes have been studied to improve electron conductance and injection because Nb has one more electron than Ti (IV) [12][13][14][15][16][17][18]. Recently, Lin et al reported the influence of TiO 2 doped with Group V-b metal atoms on the photovoltaic performance of dye-sensitized solar cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, anodic TiO 2 nanotubes have received increasing attention due to their various applications. [1][2][3][4][5] The most widely used electrolytes are F À -containing electrolytes. [6][7][8][9] Macak et al 7 indicated that the formation of a soluble complex [TiF 6 ] 2À gives rise to oxide dissolution during formation of anodic TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%